Clathrin-nanoparticles deliver BDNF to hippocampus and enhance neurogenesis, synaptogenesis and cognition in HIV/neuroAIDS mouse model - Adam, C.W (Nature Research, 2022)
Brain derived neurotrophic factor (BDNF) promotes the growth, differentiation, maintenance and survival of neurons. These attributes make BDNF a potentially powerful therapeutic agent. However, its charge, instability in blood, and poor blood brain barrier (BBB) penetrability have impeded its development. Here, we show that engineered clathrin triskelia (CT) conjugated to BDNF (BDNF-CT) and delivered intranasally increased hippocampal BDNF concentrations 400-fold above that achieved previously with intranasal BDNF alone. We also show that BDNF-CT targeted Tropomyosin receptor kinase B (TrkB) and increased TrkB expression and downstream signaling in iTat mouse brains. Mice were induced to conditionally express neurotoxic HIV Transactivator-of-Transcription (Tat) protein that decreases BDNF. Down-regulation of BDNF is correlated with increased severity of HIV/neuroAIDS. BDNF-CT enhanced neurorestorative effects in the hippocampus including newborn cell proliferation and survival, granule cell neurogenesis, synaptogenesis and increased dendritic integrity. BDNF-CT exerted cognitive-enhancing effects by reducing Tat-induced learning and memory deficits. These results show that CT bionanoparticles efficiently deliver BDNF to the brain, making them potentially powerful tools in regenerative medicine. © 2022, The Author(s).